Perception about scientific research in students of an adult program who work in a private university of Lima-2018 - Medina Coronado, Daniela (2018)
The study arises in the context of changes in the university system from the validity of the University Law 30220 that regulates the development of researches. The perception towards scientific research of the students of a program for working adults was compared according to gender, age and professional career, taking into account the following aspects: personal interest in research, link between science, society and methodology, scientific research as a way of being and general opinion about scientific research. We worked with a quantitative approach and comparative descriptive design, performing the fieldwork in the 2018-I semester with 52 students who were studying the thesis seminar, who wished to participate in the study as volunteers, applying the adapted Uribe questionnaire, Márquez, Amador and Chávez (2011). The main findings show that 42.3% of students perceive research positively, while 57.7% are indifferent or disagree. No differences were found by gender, age and professional career.